NOTES ON THE FAMILY AMPULLARIIDAE (GASTROPODA: PROSOBRANCHIA) IN THE PHILIPPINES: I. DIGESTIVE, CIRCULATORY, AND EXCRETORY SYSTEMS - ROBERTO C PAOULAYAN (BIOTROPIA, 1992)
A total of 232 ampullariid snails collected from 23 sites covering 7 islands in the Philippines were compared conchologically and 200 alcohol-preserved specimens were dissected for anatomical characteristics. Conchological comparison of the shells of the collected snails with that of identified lots from the Senckenberg Natur-museum, Frankfurt, Germany, the British Museum for Natural History, London, England, the Koninklijk Belgisch Instituut voor Natuurwetenschappen, Brussels, Belgium, and the Rijksmuseum voor Natuurwetenschappen, Leiden, Netherlands, revealed the presence of 5 species in the collected samples. These are: P. conica, P. ampullacea, P. mainitensis, P. quadrasi, and P. vittala. The latter 3 species were previously reported as being indigenous to the Philippines. Aside from characteristics of the shell, the morphology of the stomach may be useful for species discrimination. P. quadrasi and P. vittata, however, do not seem to differ anatomically from P. conica.